Self-guided accounting workbook for beginners / Adriana Shamsudin ... [et al.] - Ahmad, Khairiah; Karim, Mohd Syazwan; Mohd Pauzi, Nur Farahah; Roslan, Nurfarahin; Syed Ibrahim, Sharifah Norhafiza (UiTM Press, 2019)
This book aims to assist users to better grasp and understand basic financial accounting and reporting concepts and principles through hands on exercises .The first chapter introduces users to an overview of accounting. The beginning part of the overview deals with definition of accounting, functions and objectives of accounting information. This chapter also emphasises on exercises for users of accounting information who are internal and external users. There are three types of businesses which constitute sole proprietorship, partnership and limited companies. Users must be able to understand the characteristics of each of the business types. This chapter also touches on the differences between bookkeeping and accounting. The users can capture the overall picture of accounting process through the accounting cycle. Accounting involves bookkeeping and preparation of financial statements. Therefore, it requires adherence to accounting concepts and principles to be applied in accounting process. We provide different styles of questions to strengthen knowledge of the users to understand different accounting concepts. Towards the end of the chapter, user's knowledge on accounting classification and accounting equation is tested. Accounting classification consists of assets, liabilities, owner's equities, revenues and expenses while accounting equation covers basic accounting equation and expanded accounting equation.